Ipilimumab‐induced toxicities and the gastroenterologist. Issue 4 (April 2015) - Cheng, Robert; Cooper, Adam; Kench, James; Watson, Geoff; Bye, William; McNeil, Catriona; Shackel, Nicholas
Abstract: Ipilimumab has been shown to improve overall survival in patients with advanced melanoma. Ipilimumab acts through immune‐modulation, and is recognized to cause potentially severe immune‐related adverse events (irAEs) including dermatitis, colitis, thyroiditis, hypophysitis, and hepatitis. The acceptance of ipilimumab as a treatment for metastatic melanoma means patients will continue to be treated with this agent and gastroenterologists will be increasingly called upon to assist in managing severe autoimmune‐related hepatitis and colitis. To date, the recommendations for managing irAEs secondary to ipilimumab have been steroids at a moderate dose of prednisolone (1 mg/kg) as well as immunosuppressive agents such as mycophenolate mofetil (MMF) for steroid‐refractory hepatitis and infliximab in the management of corticosteroid‐refractory colitis. However, the dosing and the duration of immunosuppressive therapy have not been systematically studied in the setting of treating ipilimumab‐induced irAEs. Therefore, additional immune‐modifying agents and/or a change in dosing may be required to manage severe irAEs unresponsive to existing treatment recommendations. We describe a treatment paradigm illustrated by a series of five patients who experienced irAEs. In three cases of metastatic melanoma, ipilimumab‐induced hepatitis was successfully treated with high‐dose parenteral pulsed methylprednisolone. In two other melanoma patients with ipilimumab‐induced colitis, one patient had satisfactory resolution of his colitis with high‐dose corticosteroid therapy alone and the other patient required infliximab infusion. We have reviewed the current literature and management algorithms for ipilimumab‐induced irAEs. Treatment options and the rationale for their use are discussed, including the use of pulsed high‐dose steroids, MMF, azathioprine and calcineurin inhibitors.